2018
DOI: 10.15789/1563-0625-2018-6-905-912
|View full text |Cite
|
Sign up to set email alerts
|

Association of Matrix Metalloproteinases Gene Polymorphism With Clinical Manifestations of Bronchial Asthma in Children

Abstract: In the present study, we have examined association between different polymorphic variants of metalloproteinases genes and clinical manifestations of bronchial asthma in children. We observed 103 patients including 42 children with an established diagnosis of asthma. Moreover, 61 persons were examined in the control group. All patients underwent genetic testing by allele-specific polymerase chain reaction. In particular, 320A>C polymorphic locus of ММР20 gene; Val275Ala ММР20, and -8202A>G gene ММР9 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A study by Lebedenko et al found higher frequency of homozygous C/C MMP20 gene variant with 320A>C polymorphism, heterozygous MMP20 gene variant Val275Ala, and heterozygous MMP9 gene variant with −8202A>G polymorphism in patients with BA [27]. However, the frequencies of these alleles and genotypes were not significantly different in the affected children while comparing to the healthy group.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study by Lebedenko et al found higher frequency of homozygous C/C MMP20 gene variant with 320A>C polymorphism, heterozygous MMP20 gene variant Val275Ala, and heterozygous MMP9 gene variant with −8202A>G polymorphism in patients with BA [27]. However, the frequencies of these alleles and genotypes were not significantly different in the affected children while comparing to the healthy group.…”
Section: Introductionmentioning
confidence: 92%
“…Airway obstruction, characteristic to BA, results in impaired air movement, which not only requires additional physical effort during respiration but also induces remodeling mechanisms of the bronchopulmonary system [27]. An important role in this process is played by matrix metalloproteinases (MMPs), involved in the metabolism of proteins of the intercellular matrix.…”
Section: Introductionmentioning
confidence: 99%